EXPLORATION OF THE USE OF DIGITAL STORYTELLING IN SOCIAL STUDIES LEARNING: A BIBLIOMETRIC ANALYSIS STUDY - Fadli, Muhammad Rijal; Santosa, Imam; Fatonah, Khusnul; Syofyan, Harlinda; Jonuzi, Vjollca (JURNAL EDUSCIENCE, 2025)
Purpose – Digital storytelling as a form of technology integration in education has provided a new way of learning Social Studies in elementary schools. Although its effectiveness has been proven in various disciplines, the literature discussing the specific use of digital storytelling in elementary school social studies is still minimal. This study aims to fill this gap by exploring publication patterns, research trends, and collaborations related to the use of digital storytelling in elementary school social studies learning.Methodology – This study uses a quantitative method with a bibliometric analysis design to identify publication patterns, research trends, and collaboration networks based on quantitative data from journals and scientific articles. Data were obtained from publications in the 2020–2024 period indexed in Google Scholar, Scopus, and Web of Science (WoS).Findings – This study shows a notable rise in digital storytelling research in elementary schools during the first three-quarters of the analysis period, followed by a decline in the final quarter. Keyword analysis highlighted the dominance of "Digital Storytelling" (465 times), with other frequent terms including "Learner" (52), "Social Science" (40), and themes like motivation, perception, and language learning. These findings reflect a growing interest in digital storytelling for social studies, though the recent decline underscores the need for sustained strategies to maintain its relevance and effectiveness in schools.Contribution – This study's implications indicate that implementing digital storytelling in social studies learning in elementary schools has positively impacted student engagement and understanding.